Impregnasi Logam Co, Cu Dan Ni Pada Hidroksiapatit Yang Disintesis Dari Kulit Kerang Lokan (Gelonia Expansa) - Nuruzzaman Shiqhi; Yelmida A; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite (HAp, Ca10(PO4)6(OH)2) is a compound of calcium phosphate which is the main constituent of the inorganic component of human hard tissue such as bone and teeth. Hydroxyapatite (HAp) is a material used as a bone implant, adsorbents and catalysts. In this study, hydroxyapatite supported Cu catalyst was prepared using wet impregnation method. A series of Cu-HAp catalysts have been prepared by varying the amount of Cu viz., 3, 6 and 12 % w/w. The solutions were dried with stirring 350 rpm at 30 oC for 24 h. The dried samples were kept in oven maintained at 105 oC for a duration of 1 h. Finally, the dried catalyst were calcined at 500 oC for 3 h. The best results of the catalyst Cu-HAp used as the ratio to the metal Co and Ni. Impregnation results were analyzed using FTIR spectrophotometer, Surface Area Analyzer (SAA), X-ray diffraction (XRD) and Scanning Electron Microscopy - Electron Dispersive X-ray (SEM-EDX). Based on the analysis SAA synthesized HAp surface area was 17.753 m²/g, while the metal-HAp most optimal in Cu-HAp (3%) reached 31.138 m²/g, meaning that the increase in surface area reaches 75%. Results of analysis by X-ray diffraction, it shows insignificant different compare to HAp catalyst. Results of elemental analysis by SEM-EDX showed that the metal impregnation process on hydroxyapatite was quite successful. The impregnation process is influenced by stirring, drying and calcination process. Keywords: calcination, catalyst, hydroxyapatite, impregnation, metals (Cu, Co and Ni)